Identifying Scaling Pathways and Research Priorities for Kelp Aquaculture Nurseries Using a Techno-Economic Modeling Approach - Coleman, Struan; Gelais, Adam T. St.; Fredriksson, David W.; Dewhurst, Tobias; Brady, Damian C. (Frontiers in Marine Science, 2022)
Aquaculture of seaweeds, particularly in emerging farming regions such as North America, Europe, and South America, is steadily increasing. The growth of the sector has been supported by public and private R&D investment with the long-term goal of reducing farm-gate production costs. Reducing expenses would potentially allow growers to target high volume, low value markets, such as hydrocolloids, animal feeds, food thickening agents, biofuels, and carbon dioxide removal (CDR), as well as the higher value, “whole foods” markets. Regardless of the eventual fate of farmed seaweed, nursery production must increase in parallel with ocean cultivation to support the raw materials needs of the expanding industry. We quantified S. latissima (hereafter kelp) nursery production costs and identified potential barriers to cost-effective scaling using a techno-economic model (TEM). Semi-structured interviews with nursery operators in the U.S. and Europe were supplemented by an extensive literature review to parameterize the TEM. Reducing the sporophyte grow-out duration, increasing labor capacity, de-risking energy efficient flow-through systems, and optimizing tank and PVC “spool” size emerged as the most important research priorities based on our analysis. We point towards expanded gametophyte culture, and an associated policy framework to protect wild kelp population structure from monocultures, as necessary elements to support these potential improvements. The results of this work, as well as the open-source nursery TEM, are relevant to seaweed aquaculture producers, policy makers, and researchers, and can be used to guide future decision making regarding the cost-benefit of best available nursery technology.